Biodegradability assessment of aliphatic polyesters-based blends using standard methods - Moura, I. (2011)
Important information concerning polymer’s final fate in the environment can be achieved in biodegradation studies. In this context, the focus of this study was to evaluate the biodegradability of blends containing aliphatic polyesters using standard methods. Blends of high-density polyethylene, biodegradable polymer, and polyethylene modified with maleic anhydride (used as compatibilizer) were prepared in a corotating twin-screw extruder. Biodegradable polymers used were poly(lactic acid) (PLA), poly(e-caprolactone) (PCL), and Mater-Bi (thermoplastic starch with PLA or PCL). Biodegradation tests were carried out using two standard methods: (i) ISO 14851 (1999), biochemical oxygen demand in a closed respirometer and (ii) ASTM G 22-76, microbial growth of test microorganisms. Both biodegradability tests suggested that the blend containing PCL is more biodegradable than the one containing PLA. Addition of starch increased the biodegradability of the PLA blend. The biodegradability of the blends evaluated in this study by the biochemical oxygen demand method ranged from 22% (PLA 60) to 52% for corn starch/PCL 30/70 (% wt) (SPCL 70). Therefore, the blends may not be considered ‘‘readily biodegradable’’ according to the OECD standard.